2019
DOI: 10.7717/peerj.8121
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and antioxidants in the trabecular meshwork

Abstract: Glaucoma is an age-dependent disease closely related to oxidative stress and is regarded as the second leading cause of irreversible blindness worldwide. In recent years, many studies have shown that morphological and functional abnormalities of the trabecular meshwork (TM) are closely related to glaucoma, especially with respect to oxidative stress. In this review, the mechanisms of oxidative stress in the TM and treatment strategies for this condition, including strategies involving antioxidants, noncoding R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 107 publications
1
25
0
Order By: Relevance
“…The trabecular meshwork is an avascular, complex connective tissue component that can effectively regulate the outflow of aqueous humor [32]. The sources of trabecular meshwork oxidative stress include ultraviolet (UV)-based byproducts of the anterior chamber, excess ROS accumulation [33], and the imbalance between oxidants and antioxidants [6,34]. Studies have shown that in patients with POAG, the trabecular meshwork is exposed to ROS in aqueous humor, which suggests that ROS may have a causative role in glaucoma at the level of trabecular meshwork cells [35,36].…”
Section: Oxidative Stress Glaucoma Trabecular Meshwork Cells and Nrf2mentioning
confidence: 99%
See 3 more Smart Citations
“…The trabecular meshwork is an avascular, complex connective tissue component that can effectively regulate the outflow of aqueous humor [32]. The sources of trabecular meshwork oxidative stress include ultraviolet (UV)-based byproducts of the anterior chamber, excess ROS accumulation [33], and the imbalance between oxidants and antioxidants [6,34]. Studies have shown that in patients with POAG, the trabecular meshwork is exposed to ROS in aqueous humor, which suggests that ROS may have a causative role in glaucoma at the level of trabecular meshwork cells [35,36].…”
Section: Oxidative Stress Glaucoma Trabecular Meshwork Cells and Nrf2mentioning
confidence: 99%
“…The reduction of total reactive antioxidant capacity in patients with POAG is reduced by 60-70%, which indicates that these patients might be more susceptible to damage from oxidative stress [6,43]. In 2017, Cheng et al found that compared with normal human trabecular meshwork cells, Nrf2 expression was down-regulated in glaucomatous trabecular meshwork cells, e921514-2 and in both cell types, the overexpression of Nrf2 promoted cell viability and reduced cell apoptosis [44].…”
Section: Oxidative Stress Glaucoma Trabecular Meshwork Cells and Nrf2mentioning
confidence: 99%
See 2 more Smart Citations
“…The cells were collected 24 hours after the H2O2 treatment and levels of few selected gene transcripts form the our GWAS using quantitative RT-PCR and gene expression primers ( Supplementary Table) and following previously published protocols. [94][95][96] The relative gene expression was compared against control (no treatment) to obtain normalized gene expression. Expression levels (±SEM) were calculated by analyzing at least three independent samples with replicate reactions and presented on an arbitrary scale that represents the expression of relevant genes compared to the housekeeping gene ACTB.…”
Section: Evaluating Oxidative Stress In Tm and Ipsc-rgcsmentioning
confidence: 99%